2000
DOI: 10.1002/hep.510310304
|View full text |Cite
|
Sign up to set email alerts
|

Local arterial vasoconstriction induced by octreotide in patients with cirrhosis

Abstract: Peripheral vasodilation initiates the hyperdynamic circulation in cirrhosis. Somatostatin and its analogues, such as octreotide, have a vasoconstrictive effect in cirrhotic patients and experimental animals with portal hypertension. The exact mechanism of octreotide-induced vasoconstriction remains unknown. To investigate whether octreotide produces vasoconstriction through suppression of vasodilatory peptides, such as glucagon, or through a local effect, we evaluated the effect of an intra-arterial dose on fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
2
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 45 publications
2
36
2
1
Order By: Relevance
“…14,15,[19][20][21] The vasoconstrictive effect of octreotide on the splanchnic circulation is thought to be mediated partly by an inhibition of glucagon secretion 22 ; a direct effect on the smooth muscle vasculature has also been suggested. 23 We did not find any decrease in fasted glucagon plasma levels after octreotide infusion. Previous studies have shown that octreotide could reduce glucagon plasma levels after acute intravenous 17 or subcutaneous administration 14 or after chronic subcutaneous administration.…”
Section: Discussioncontrasting
confidence: 50%
“…14,15,[19][20][21] The vasoconstrictive effect of octreotide on the splanchnic circulation is thought to be mediated partly by an inhibition of glucagon secretion 22 ; a direct effect on the smooth muscle vasculature has also been suggested. 23 We did not find any decrease in fasted glucagon plasma levels after octreotide infusion. Previous studies have shown that octreotide could reduce glucagon plasma levels after acute intravenous 17 or subcutaneous administration 14 or after chronic subcutaneous administration.…”
Section: Discussioncontrasting
confidence: 50%
“…When this SRIF receptor activation is prevented or reduced by an SRIF receptor antagonist such as c-SOM or SRIF antiserum, nociceptive behavior (flinching) results. However, we cannot completely rule out the possibility that c-SOM-induced nociceptive behaviors might be through indirect mechanisms, such as promotion of proinflammatory cytokines (ten Bokum et al, 2000) or blood flow changes (Chatila et al, 2000). However, c-SOM produces significant activity in nociceptors in the in vitro skin-nerve preparation in which there is no blood flow; thus, blood flow changes are an unlikely possibility.…”
Section: Discussionmentioning
confidence: 90%
“…37 However, the experimental studies on the effects of octreotide on vascular reactivity have all been performed on splanchnic vessels, and a direct effect of octreotide in other areas of the vasculature has indeed been suggested by a recent study in cirrhotic patients. 10 In addition, the experimental studies indicate that an inhibitory effect of octreotide on renin-aldosterone secretion as well as normalization of arginin-vasopressin may be responsible for the beneficial effects on sodium excretion. 22,35,36 The results of these experimental studies could only be reproduced in a clinical setting in the part of increased mean arterial pressure, although serum concentrations of octreotide were clearly within the therapeutic range of 1,000 to 3,000 ng/L in the study period.…”
Section: Discussionmentioning
confidence: 99%